THE IMPLEMENTATION OF STERILIZATION AND TRAFFIC MANAGEMENT OF PASSENGERS AND VEHICLES AT AIR PUTIH FERRY PORT BENGKALIS REGENCY OF RIAU PROVINCE - Irwan Irwan; Paulina M Latuheru; Rahmatul Safitri Pribadi (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2021)
The Air Putih Ferry Port is one of the ports in Bengkalis Regency, Riau Province which serves the Air Putih – Sungai Selari route. The Air Putih Ferry Port is very important to support economic development in Bengkalis Regency. The port for carrying out crossing transportation activities is expected to provide safe, orderly, and smooth services. Currently, the sterilization and management of passenger and vehicle traffic have not been implemented properly. At the Air Putih Ferry Port itself, passengers and vehicles buy tickets at the same counter. The delivery person/pick up is free to enter the pier. In addition, there is also a crossing at the entrance to the ferry port. The method used to analyze the existing problems in the analysis of sterilization at the Air Putih Ferry Port, analysis of traffic management, and analysis of facilities that can support the application of sterilization and management of passenger and vehicle traffic at the Air Putih Ferry Port. Based on this analysis, it can be concluded that the sterilization of the ferry port has not been implemented so that the management of passenger and vehicle traffic has not been orderly and orderly. In addition, the supporting facilities for sterilization and management of passenger and vehicle traffic at the Air Putih Ferry Port are considered still not optimal in their use. To create an orderly and safe ferry port, what can be done is to implement the sterilization of the ferry port and the management of passenger and vehicle traffic at the Air Putih Ferry Port and to support the sterilization and management of passenger and vehicle traffic, it is necessary to optimize supporting facilities such as signs, markers, as well as officers who play a role in the security and order of the ferry port.